Paraguay Poverty Assessment : Determinants and Challenges for Poverty Reduction - World Bank (Washington, DC, 2013)
This report provides technical assistance and capacity building on the poverty measurement methodology of the Paraguayan government. The report makes several policy recommendations concerning urban labor market trends and opportunities for employment, rural factor markets and poverty, and ex-ante evaluation of the expansion of cash transfer programs in Paraguay. The report concludes that in order to increase productivity it is important to increase the quality of education and give incentives for the youth to finish their formal education. Also, poverty reduction policies need to be targeted at the rural poor specifically by increasing access to land ownership.